Sustainability through Workshops: A Case Study of People’s Campus - Bajracharya, Rajan Bilas; Raya, Rajendra; Pandit, Rojesh (Community College Research Journal, 2025)
Sustainability is one, but not the only issue that has been identified as the major problem the world faces today. Nevertheless, business education in the poorest countries like Nepal often neglects sustainability topics and therefore cannot be considered effective. The present research uses People's Campus in Kathmandu as a case study to find out if experiential workshops can be of great help in the case of teaching sustainable business practices. The study map out the workshops in terms of content, delivery, engagement, learning outcomes, and logistics, it then assesses the effectiveness of each workshop through a descriptive survey method and a standardized questionnaire with a 5-point Likert scale. The author analyzed the quantitative data from participant comments by working with mean score evaluations and frequency distributions. The findings reveal that the workshops incredibly empowered the participants with great tools for sustainable business planning and also the communication of the relevant information. The tools received a rating more than 75% of the participants as beneficial and everyone considered the material to be appropriate. However, a lot of the ratings were implicit, reflecting that the areas of participation, facilitator communication, and session measurement are the ones where more attention should be given. A few people requested more detailed and personalized content but on the whole, the learning effects were very satisfactory and 68% of the participants stated they had become more confident. The logistics were rated the highest among the different aspects, for instance, the venue and the materials. The study confirms the role of experiential, active learning in business education and additionally contributes to the very limited literature on sustainability education in South Asia. It also presents the very useful recommendations for workshop design improvement, such as more efficient logistics, better interaction tactics, and flexible content delivery. The outcome of the research portrays the use of workshops as a large-scale method of incorporating sustainability into business education in Nepal and similar environments.